Pengaruh Audit Tenure, Rotasi Audit, dan Ukuran Perusahaan Terhadap Kualitas Audit - Nazwar, Muh. Naufal; Nurhidayana, Nurhidayana; Ryketeng, Masdar; Ginting, Chris Dayanti Br; Rahman, Ahmad Nashiruddin Mushoddiq (Bata Ilyas Journal of Accounting, 2024)
The purpose of this study is as a means of knowing the length of time a financial auditor has worked, auditor rotation, and company size when associated with audit quality in digital-based companies listed on the Indonesia Stock Exchange. The material in the study was selected according to the financial and annual reports of the companies on the Indonesia Stock Exchange website. The study used a sample of 12 companies from the 2021-2023 period. The sampling technique is one of the research approaches implemented in this study. Quantitative secondary data is the type used. Furthermore, one of the methods used is multiple regression evaluation. Thus, from the research that has been carried out, it can be concluded that the length of time a financial auditor has a negative impact on the level of audit quality, audit rotation has no effect on audit quality, and company size has a positive impact on audit quality.Tujuan penelitian ini adalah sebagai sarana untuk mengetahui lamanya masa kerja auditor keuangan, rotasi auditor, dan ukuran perusahaan bila dikaitkan dengan kualitas audit pada perusahaan berbasis digital yang terdaftar di Bursa Efek Indonesia. Materi dalam penelitian dipilih berdasarkan laporan keuangan dan laporan tahunan perusahaan yang ada di website Bursa Efek Indonesia. Penelitian ini menggunakan sampel sebanyak 12 perusahaan periode 2021-2023. Teknik pengambilan sampel merupakan salah satu pendekatan penelitian yang diterapkan dalam penelitian ini. Jenis data yang digunakan adalah data sekunder kuantitatif. Selanjutnya salah satu metode yang digunakan adalah evaluasi regresi berganda. Dengan demikian dari penelitian yang telah dilakukan dapat disimpulkan bahwa lamanya masa kerja auditor keuangan berpengaruh negatif terhadap tingkat kualitas audit, rotasi audit tidak berpengaruh terhadap kualitas audit, dan ukuran perusahaan berpengaruh positif terhadap kualitas audit. The purpose of this study is as a means of knowing the length of time a financial auditor has worked, auditor rotation, and company size when associated with audit quality in digital-based companies listed on the Indonesia Stock Exchange. The material in the study was selected according to the financial and annual reports of the companies on the Indonesia Stock Exchange website. The study used a sample of 12 companies from the 2021-2023 period. The sampling technique is one of the research approaches implemented in this study. Quantitative secondary data is the type used. Furthermore, one of the methods used is multiple regression evaluation. Thus, from the research that has been carried out, it can be concluded that the length of time a financial auditor has a negative impact on the level of audit quality, audit rotation has no effect on audit quality, and company size has a positive impact on audit quality.